Historical DNA documents long‐distance natal homing in marine fish. Issue 12 (14th March 2016) - Bonanomi, Sara; Overgaard Therkildsen, Nina; Retzel, Anja; Berg Hedeholm, Rasmus; Pedersen, Martin Wæver; Meldrup, Dorte; Pampoulie, Christophe; Hemmer‐Hansen, Jakob; Grønkjær, Peter; Nielsen, Einar Eg
Abstract: The occurrence of natal homing in marine fish remains a fundamental question in fish ecology as its unequivocal demonstration requires tracking of individuals from fertilization to reproduction. Here, we provide evidence of long‐distance natal homing (>1000 km) over more than 60 years in Atlantic cod ( Gadus morhua ), through genetic analysis of archived samples from marked and recaptured individuals. Using a high differentiation single‐nucleotide polymorphism assay, we demonstrate that the vast majority of cod tagged in West Greenland and recaptured on Icelandic spawning grounds belonged to the Iceland offshore population, strongly supporting a hypothesis of homing. The high degree of natal fidelity observed provides the evolutionary settings for development of locally adapted populations in marine fish and emphasize the need to consider portfolio effects in marine fisheries management strategies. Abstract : See also the Perspective by Bentzen and Bradbury